2006
DOI: 10.1111/j.1524-4725.2006.32062.x
|View full text |Cite
|
Sign up to set email alerts
|

Periungual Basal Cell Carcinoma: Case Report and Literature Review

Abstract: Case report and review of the English literature of nail unit basal cell carcinoma. RESULTS In addition to the currently described patient, 17 other patients with nail unit basal cell carcinoma have been reported. The tumor occurred approximately 3 times more often on the fingers then on the toes and had a slight predilection to occur in men. Ulceration, noted in more than one-half of patients, was the most common presentation of nail unit basal cell carcinoma. Mohs micrographic surgery. Often with second inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…[54][55][56][57] It typically presents in adults and has been associated with exposure to ultraviolet radiation. 54,58,59 BCC occasionally is reported in children.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56][57] It typically presents in adults and has been associated with exposure to ultraviolet radiation. 54,58,59 BCC occasionally is reported in children.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation varies from onycholysis[610] to longitudinal melanonychia,[1217] and the most common sign of the disease is ulceration[7814161820212426] around and of the nail plate, as seen in our subject.…”
Section: Discussionmentioning
confidence: 90%
“…Male: female ratio was 1.8:1. The thumb was the most frequently affected site[568912131519242628] and the hallux was reported in five cases. [1118212227] The right middle finger was involved in three cases[41620] and both hands were affected with almost similar frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Skin cancer, predominantly basal cell carcinoma and squamous cell carcinoma, have accounted for about 40% of all cancers in the United States and their frequency has been increasing [1]. However, the nail unit is a very uncommon site for basal cell carcinoma to develop [2,3,4]. In 2006, Martinelli et al[ 2] reviewed the English literature and found only 17 patients with a basal cell carcinoma at this location.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nail unit is a very uncommon site for basal cell carcinoma to develop [2,3,4]. In 2006, Martinelli et al[ 2] reviewed the English literature and found only 17 patients with a basal cell carcinoma at this location.…”
Section: Introductionmentioning
confidence: 99%